2017
DOI: 10.1109/mmul.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Open Symphony: Creative Participation for Audiences of Live Music Performances

Abstract: Most contemporary Western performing arts practices restrict creative interactions from audiences. Open Symphony is designed to explore audience-performer interaction in live music performance assisted by digital technology. Audiences can conduct improvising performers by voting for various musical 'modes'. Technological components include a web-based mobile application, a visual client displaying generated symbolic scores, and a server service for the exchange of creative data. The interaction model, app and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 15 publications
(17 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, we will extend the results of this study for the application of MHWs for performer-performer interactions in remote settings. Other types of interactions will also be addressed such as between performers and Musical Things [11], as well as between performers and audience members (see e.g., [37]), in co-located or remote settings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we will extend the results of this study for the application of MHWs for performer-performer interactions in remote settings. Other types of interactions will also be addressed such as between performers and Musical Things [11], as well as between performers and audience members (see e.g., [37]), in co-located or remote settings.…”
Section: Discussionmentioning
confidence: 99%
“…With Open Symphony by Wu et al (2017) audience members could make creative decisions and generate scores, the musicians were playing in real-time. However, the authors reported that spectators still 'wished to have more control' although some others 'felt challenged by the novelty'.…”
Section: Related Smartphone Research Focimentioning
confidence: 99%
“…Smartphones have become a key device for large-scale audience participation in live music both for scientific studies as well as performing artists, e.g. Hirabayashi and Eshima (2015), Wu, Zhang, Bryan-Kinns, and Barthet (2017), Lee, Willette, Koutra, and Lasecki (2019) or Matuszewski, Schnell, and Bevilacqua (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Semantic Audio also includes rich conceptualisation of audio metadata including the composition, production and consumption of audio and music [35]. The field has numerous applications, from navigation in large audio collections through automated tagging [36], through music recommendation [37] to intelligent music production [38] and participatory music performance [39], [40].…”
Section: Semantic Audio and Ontologiesmentioning
confidence: 99%